Comparison of dyslipidemia incidence in Chinese early-stage breast cancer patients following different endocrine therapies: A population-based cohort study - Wang, Junren; Yin, Jin; Qiu, Jiajun; Jiang, Jingwen; Hu, Yao; Zhu, Kunrui; Zheng, Hong; Luo, Ting; Zhong, Xiaorong (Frontiers in Endocrinology, 2022)
Background The impact of endocrine therapy on blood lipid in Chinese breast cancer patients, especially for premenopausal breast cancer patients, are still lack of large-scale real-world research evidence. Based on the large breast cancer cohort at West China Hospital, we aimed to compare the risk of dyslipidemia induced by different endocrine and menopause status. Methods 1883 early breast cancer (EBC) patients registered in Breast Cancer Information Management System (BCIMS) from October 2008 to April 2017, receiving mono endocrine therapy (selective estrogen receptor modulator (SERM), aromatase inhibitor (AI), with or without ovarian function suppression) with initial normal blood lipids were included. Dyslipidemia was defined as abnormality of cholesterol/LDL/ HDL/triglyceride. Risk accumulation function was used to calculate the incidence of dyslipidemia to assess absolute risk, and the multivariate COX regression model was used to calculate the relative risk of dyslipidemia between groups. Results EBC patients were followed up for 60 months to monitor their blood lipid levels. The accumulated 5-year incidence of dyslipidemia in menopausal patients was higher than that in premenopausal patients (Adjusted HR [95%CI], 1.29 [1.04 – 1.59], 42.6 % vs 32.6%, P=0.0186). In premenopausal patients, the risk of abnormal TC in OFS+AI group was significantly higher than SERM group (adjusted HR, 3.50 [ 1.74 - 7.02], P<0.001, 5-year abnormal rate 22.0% vs 3.5%), and that of abnormal LDL-C was also increased (adjusted HR, 6.71 [ 3.16 – 14.26], P<0.001, 5-year abnormal rate 12.2% vs 1.4%). In menopausal patients, the risk of abnormal TC or LDL-C showed the similar trend in AI group compared to SERM group. Conclusions Dyslipidemia was common in both premenopausal and postmenopausal Chinese EBC patients receiving endocrine therapy. Irrespective of menopause, AIs treatment causes higher risk of TC/LDL-C dyslipidemia than SERM.